2022
DOI: 10.3390/plants11101322
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Mutagenic Effectiveness and Efficiency of Gamma Rays and Sodium Azide in Inducing Chlorophyll and Morphological Mutants of Cowpea

Abstract: Mutagenic effectiveness and efficiency are the most important factors determining the success of mutation breeding, a coherent tool for quickly enhancing genetic diversity in crops. However, conclusive evidence of using an effective and efficient dose of gamma (γ) rays and sodium azide (SA) for genetic improvement is scant. The present study assesses genetic diversity in M2 mutants of cowpea and evaluates mutagenic effectiveness and efficiency of the single and combination doses of γ rays and SA. In M0 generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…These mutants are of no economic value but their frequency was deliberated to measure the effectiveness and efficiency of induced mutation by gamma irradiation and also served as a primary index for evaluating the genetic alteration which was caused by the mutagens. A wide spectrum of leaf mutants was found in gamma-irradiated treatment and has been reported earlier in green gram (31) and in cowpea (32). The effectiveness and efficiency of mutagens are important parameters to exploit induced mutagenesis for crop improvement.…”
Section: Discussionmentioning
confidence: 63%
“…These mutants are of no economic value but their frequency was deliberated to measure the effectiveness and efficiency of induced mutation by gamma irradiation and also served as a primary index for evaluating the genetic alteration which was caused by the mutagens. A wide spectrum of leaf mutants was found in gamma-irradiated treatment and has been reported earlier in green gram (31) and in cowpea (32). The effectiveness and efficiency of mutagens are important parameters to exploit induced mutagenesis for crop improvement.…”
Section: Discussionmentioning
confidence: 63%
“…Induced mutagenesis is an effective method for improving agronomic traits and genetic variability of important crops such as cowpea (27,28) lentil (29,30) faba bean (31,32), chickpea (33,34) urd bean (35,36), bean (37), rice (38,39) black cumin (40,41), fenugreek (42), and finger millet (43). In the present study on finger millet (Paiyur-2), all the studied morphological and quantitative traits increased in mutagenized population treated with 400 Gy to 600 Gy doses.…”
Section: Discussionmentioning
confidence: 99%
“…The seed number is also an important yield attributing trait, and mutants with increased seeds per pod should be prioritized in selection programs. Earlier studies also reported increased seeds per pod in mutagenized crops [ 68 ]. In plant breeding programs, yield improvement is the ultimate aim of plant breeders and geneticists.…”
Section: Discussionmentioning
confidence: 94%